Publications generated from abstracts presented at the 28thCongresso Brasileiro de Patologia and the 28th Congreso de la Sociedad Latinoamericana de Patologia, in 2011 - Alberto S. Paes; Thiago A. C. C. Teixeira; Gabriel V. S. Tabosa; Rafael M. Luna; Lorena do Socorro L. Saraiva (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTIntroduction:The medical congresses are an efficient way, although restricted, to expose the scientific production of a particular specialty. However, the number of complete articles published resulting from papers presented at congresses and published as abstracts is much lower than the number of papers presented during the meetings.Objective:Scale the number of complete articles published and indexed in online databases, from 2012 to January 2015, originally presented at the 28th Congresso Brasileiro de Patologia (28th Brazilian Congress of Pathology) and the 28th Congreso de la Sociedad Latinoamericana de Patología (28th Latin American Society of Pathology Congress).Material and method:In the meetings mentioned 701 papers were presented and their abstracts published in the congresses annals. An observational retrospective study was conducted consulting the following biomedical databases: Scientific Electronic Library Online (Scielo) and US National Library of Medicine on the National Institutes of Health (PubMed), with the help of the Google search engine, based on the article title and the list of authors.Results:From 701 studies analyzed, 635 (90.6%) were from Brazilian institutions, 60 (8.6%) from foreign institutions, and six (0.8%) did not identified their home institutions. There were found 63 (8.8%) complete articles published and indexed to consulted databases. International journals were the destination of 38 (60.3%) publications.Conclusion:The number of complete articles published in Pathology area arising from the papers presented in the studied meetings in the first three years after the meetings is relatively small. This number is low compared with other international conferences; however, it is higher than some Brazilian medical congresses analyzed in similar studies.